THE ANALYSIS OF SABO DAM PERFORMANCE AS A SEDIMENT CONTROL STRUCTURE IN PUTIH RIVER, MT. MERAPI - Andre Wisoyo (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2012)
Mt. Merapi’s eruption which occurred on 26 October 2010 had disadvantageous impact for human life that live surrounds it. The primary disaster was pyroclastic cloud that destroyed villages surround it. In addition, the secondary disaster continuously became a threat for human life around the rivers that destroyed at Mount Merapi. One of the secondary disasters is Putih River’s volcanic material overflowing into Yogyakarta-Magelang Highway. The series of Sabo dam which had been built along the river could not handle that phenomenon. Sabo dam was built and expected to accommodate volcanic material or at least to resist the velocity of volcanic material (sediment controlling), so the damage caused by the flow became relatively small. However, this function could not work at that phenomenon. In order to know the function of sediment control of Sabo dam in Putih River, it is necessary to study the performance of Sabo dam. This research used Kanako software ver. 2.04 and reviewed Sabo dam PU-D1 Mranggen and PU-C8 Ngaglik. There were four simulated scenarios in this research: a scenario without Sabo dam; with Sabo dam PU-D1 Mranggen; with Sabo dam PU-C8 Ngaglik, and the last with two of Sabo dams. The simulation was based on 23 January 2011 event and simulated for 18.000 s. From this research, it can be concluded that Sabo dam PU-D1 Mranggen can reduce the total volume passing through about 43,998.6 m3 or 1.53 % for 5 hours, and reduce the sediment volume that passing through about 28,482 m3 or 52.59 % for 5 hours. Sabo dam PU-C8 Ngaglik can reduce the total volume that passing through about 255.6 m3 or 0.01 % for 5 hours, and reduce the sediment volume that passing through about 124.8 m3 or 0.33 % for 5 hours, and Sabo dam PU-D1 Mranggen and PU-C8 Ngaglik in series can reduce the total volume that passing through about 2,340.6 m3 or 0.08 % for 5 hours, and reduce the sediment volume that passing through about 157.8 m3 or 0.41 % for 5 hours